2020
DOI: 10.4314/gjas.v55i2.4
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and adoption levels of improved smoking oven among fish processors in Lagos Lagoon, Nigeria

Abstract: This paper investigated awareness and adoption levels of improved smoking oven among fish processors in four fishing communities along Lagos Lagoon, Nigeria. Multi-stage sampling procedure was used to select 153 respondents who were engaged in fish smoking. Data collected using structured interview guides were subjected to descriptive and inferential analyses. Results revealed that majority of the respondents were young, married women with average fish smoking experience of 22.6 years. Majority (90.8%) of them… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…3,11 Slips, trips, falls, and exposure to loud noises are major physical dangers in handling facilities, while chemical mishaps, solvents, vapors, fumes, and unburned hydrocarbons are common chemical hazards. 3 Occupational dangers are produced by mechanical factors influencing the musculoskeletal system, whereas biological hazards are caused by parasite infection, bacteria or viruses, or injuries from animals such as shark or crocodile bites. 3 Fatal accidents constitute an inherent and unsolved problem among fishermen.…”
Section: Environmental Health Insightsmentioning
confidence: 99%
See 2 more Smart Citations
“…3,11 Slips, trips, falls, and exposure to loud noises are major physical dangers in handling facilities, while chemical mishaps, solvents, vapors, fumes, and unburned hydrocarbons are common chemical hazards. 3 Occupational dangers are produced by mechanical factors influencing the musculoskeletal system, whereas biological hazards are caused by parasite infection, bacteria or viruses, or injuries from animals such as shark or crocodile bites. 3 Fatal accidents constitute an inherent and unsolved problem among fishermen.…”
Section: Environmental Health Insightsmentioning
confidence: 99%
“…3 Occupational dangers are produced by mechanical factors influencing the musculoskeletal system, whereas biological hazards are caused by parasite infection, bacteria or viruses, or injuries from animals such as shark or crocodile bites. 3 Fatal accidents constitute an inherent and unsolved problem among fishermen. 12 Fish processing is a series of events that spans the entire process of handling fish and fish products, from harvesting through customer delivery.…”
Section: Environmental Health Insightsmentioning
confidence: 99%
See 1 more Smart Citation
“…The drum smoking methods, although still practiced in some areas, is gradually fading away with the emergence of the banda methods. These methods used for fish smoking are not new to literature as confirmed by Alabi,et al (2020) that traditional methods such as mud, box and drum ovens are the dominant fish smoking methods in Nigeria. Although, Alabi et al (2020) reported low adoption of improved technologies of fish smoking in Lagos, Nigeria; however, with the growing aquaculture activities in Kainji Lake Basin, there seems to be a gradual adoption of a better, safer fish smoking method.…”
Section: Methods Used In Fish Processingmentioning
confidence: 99%
“…The idea of fish processing in Nigeria was adopted to reduce post-harvest losses because of the perishability nature of fish which undergoes spoilage as soon as it is harvested (Amos and Ibrahim, 2017). Fish processing could be done through smoking, drying, refrigeration, frying etc; though, smoking is the principal fish processing technique in Nigeria (Alabi, et al, 2020). Fishes that are smoked have a great sensory characteristic such as good taste, flavour and texture and are highly enjoyed in diets (Puke and Galoburda, 2020).…”
Section: Introductionmentioning
confidence: 99%